Organizational models of ophthalmic observation of premature children in pediatric follow-up - E. I. Saidasheva; E. V. Plotnikova; S. V. Bilichenko; V. I. Shilina (Российский офтальмологический журнал)
Purpose: to assess the organizational effectiveness of ophthalmic observation of premature infants in pediatric follow-up in St. Petersburg. Material and methods. We analyzed the reports submitted by city interdistrict ophthalmological facilities for retinopathy of prematurity (ROP) and the observation department for premature infants for the period from July 1, 2018 to July 1, 2021 available at the children's multidisciplinary hospital. Results. In St. Petersburg, 6 interdistrict ophthalmological facilities perform regular monitoring of ROP children and a daytime in-patient clinic offers interdisciplinary treatment and early rehabilitation of infants with perinatal pathology accompanying severe prematurity. The data on the frequency of ROP and other visual disorders in children born prematurely are presented. Conclusions. Interdistrict observation facilities are a modern form of regular ophthalmic follow-up of premature infants of risk groups or ROP infants who live in conditions of a large city. A promising observation model of children with combined perinatal pathology and severe prematurity is the setting of a department (daytime in-patient facility) in the children's multidisciplinary hospital. This allows assessing the general health of this critical group of population" and ensure a timely start of combined interdisciplinary treatment and medical rehabilitation.